2006
DOI: 10.1117/1.2343208
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration mechanism of optical clearing in tissue

Abstract: Previous studies identified various mechanisms of light scattering reduction in tissue induced by chemical agents. Our results suggest that dehydration is an important mechanism of optical clearing in collagenous and cellular tissue. Photographic and optical coherence tomography images indicate that air-immersed skin and tendon specimens become similarly transparent to glycerol-immersed specimens. Transmission electron microscopy images reveal that dehydration causes individual scattering particles such as col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
132
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 23 publications
1
132
0
1
Order By: Relevance
“…The aqueous solutions of glycerol are immersion liquids widely used as OCAs due to their efficiency, availability, and biocompatibility [1][2][3][4][5][6][7][8]. Unfortunately, in spite of the wide use of glycerol for controlling the tissue optical parameters, there is no unambiguous answer to the question about the optimal concentration of the glycerol solution.…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous solutions of glycerol are immersion liquids widely used as OCAs due to their efficiency, availability, and biocompatibility [1][2][3][4][5][6][7][8]. Unfortunately, in spite of the wide use of glycerol for controlling the tissue optical parameters, there is no unambiguous answer to the question about the optimal concentration of the glycerol solution.…”
Section: Introductionmentioning
confidence: 99%
“…Biological tissues can become subject to compression in several ways, including physiologically (pressure exerted on vessel walls during the cardiac cycle (7) and cellular mechanotransduction (8,9)), pathologically (traumatic injuries (10)) clinically (edema monitoring for dialysis patients (11), electrosurgery (12), body water and fat detection (5), and soft-tissue healing techniques (13)), and in basic research (optical clearing in tissues (14) and probe characterization (15)). Even fields that would at first seem to fall far abreast of this specific discussion have added relevance given their synthesis of passive electrical properties with the mechanical properties of materials under examination including certain realms of agricultural research focused on meat quality assessment (16,17) and mineralogical investigations of rocks (18).…”
Section: Introductionmentioning
confidence: 99%
“…3 demonstrates that decreasing the tissue temperature resulted in decreasing the µ's and, therefore, increasing the PI and TI which means enhancement of photon density in the dermis. As described in previous studies, such results may be caused by the modification of collagen fiber structure, degradation of cellular components, and change of the refractive index of intercellular fluid [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 96%
“…Rylander et al [18] and Yu et al [19] that skin dehydration is the prominent mechanism of OTC and Yeh et al [20] suggested that the reversible change of both collagen structure and size can affect OTC. In recent in-vivo studies, Ghosn et al monitored and quantified the permeability rate of glucose solutions in in-vivo monkey skin by using OCT [21], and Wen et al reported that the thickness decrease of dermis and regular arrangement of tissue fibers were prominent OTC mechanisms [22].…”
Section: Introductionmentioning
confidence: 99%